PERANCANGAN APLIKASI SPJ PERJALANAN DINAS PADA DINAS KEPENDUDUKAN PENCATATAN SIPIL KABUPATEN PASAMAN - Arman,Gusrino Yanto Nelfira,Rahmi (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
The Civil Registration Population Department is one of the existing Government Institutions inPasaman Regency of West Sumatra Province. Department of Population Civil Registration InMaking Letter of Accountability (SPJ) Travel Service Office of Population and Civil RegistrationPasaman not utilize the information system technology optimally. Process Pengentrian and DataProcessing only use Microsoft Office Word and Microsoft Office Excel applications so that theprocess of preparing the SPJ to be not integrated, ineffective and inefficient. To overcome theproblem, the development of Information System can accelerate the process of data entry andprocessing. Information System SPJ Travel Agency at the Department of Population and CivilRegistration Pasaman District is designed by using Java Programming Language to support dataprocessing, so that the process of preparation of SPJ Travel Office integrated, effective andefficient can be achieved.Keywords: SPJ Travel Agency, Information System.